IMPLEMENTASI LOGIKA FUZZY TAHANI UNTUK MODEL SISTEM PENDUKUNG KEPUTUSAN EVALUASI KINERJA KARYAWAN - Taufiq, Ghofar (Jurnal Pilar Nusa Mandiri, 2016)
The main purpose of employee performance evaluation is to monitor and determine the performance of an employee in a company, whether it is working optimally or not to conduct an assessment of the criteria for the performance of an employee . As for the criteria regarding the evaluation of staff performance will be evaluated in this study was the presence, quality of work , creativity , technical skills , communication skills and attitude . These criteria still have data that is ambiguous ( vague ) . By Tahani fuzzy , ambiguous data that can be processed to remove ambiguity data. The aim of this study is to apply fuzzy logic with Tahani method for evaluating employee performance and yield ranking of employee performance evaluation results . While the outcome of this research is a model of a decision support system for employee performance evaluation with fuzzy logic approach Tahani methods that provide information about the results of the performance evaluation of employees .